PERAN WORLD WIDE FUND FOR NATURE (WWF) DALAM MENGATASI EKSPLOITASI HIU TIKUS (THRESHER SHARKS) DI INDONESIA TAHUN 2007-2013 - Leisubun, Rosalia (Global and Policy Journal of International Relations, 2015)
ABSTRACTIndonesia has signed an agreement IOTC (Indian Ocean Tuna Commission), this means that Indonesia has been a member of IOTC, contained in resolution 10/12 of IOTC agreement that protects mice that mean shark shark rat can not be arrested or merchantability. However, in reality the condition of fisheries in Indonesia is dominated by mainly shark shark catches mice. WWF as international organizations have a very important role in this regard is as INGO advocacy. In this issue investigated by using variables that variable direct lobbying and grassroots lobbying, this paper analyzes the role of WWF in encouraging government policies to address the exploitation of sharks rats in Indonesia by using qualitative methods Explanative-equipped with the concept of lobbying and decision making.Key Words: WWF, INGO advocacy, Direct Lobbying, Grassroots Lobbying, Government PolicyDOI:https://doi.org/10.33005/jgp.v3i01.1963